Balanced Scorecard Approach At Regional General Hospital As Regional Public Services Agencies - Emirallisa, Sindi; Rizani, Fahmi; Limarjani, Sustinah (Yayasan Cita Cendekiawan Al Khwarizmi, 2023)
The research aims to analyze the performance of the Regional Public Service Agency specifically at the A.M Parikesit’s Tenggarong Regional General Hospital, East Kalimantan, using the Balanced Scorecard as its approach. The type of reserach used is descriptive quantitative and the data collected in the form of primary and secondary data. Secondary data was obtained from financial statements, medical record reports, HR and Training reports and patient questionnaire data. Meanwhile, primary data were obtained from questionnaires of hospital employees distributed. The respondents of the study were 100 patient respondents and 188 employee respondents. The results showed that the performance of A.M. Parikesit Hospital based on the Balanced Scorecard approach was quite good. There are 2 perspectives that are classified as good and there are 3 other perspectives that are classified as less good. Of course, this is a reference for future development and improvement. However, this means that in each perspective special attention is needed, so that the weaknesses that occur can be evaluated and improved.